Modeling the physiochemistry of levoglucosan during cellulose pyrolysis - Bai, Xianglan; Brown, Robert C. (Journal of analytical and applied pyrolysis, 2014)
•Physiochemistry of liquid levoglucosan during pyrolysis is modeled.•Kinetic parameters of evaporation and polymerization of levoglucosan are measured.•Activation energies of evaporation and polymerization are 92kJ/mol and 139kJ/mol.•Increased sample mass enhances the polymerization rather than the evaporation.•Higher heating rate does more to enhance the polymerization than the evaporation. Levoglucosan is the main product of cellulose pyrolysis and also a potential platform chemical for biobased products. Previously we reported that during cellulose pyrolysis, levoglucosan is initially a liquid that is subject to the competing processes of evaporation and polymerization. While levoglucosan that evaporates can be transported out of the pyrolysis reactor and recovered, the non-volatile anhydro-oligosaccharides are trapped within the reactor where they dehydrate to char and low molecular weight compounds. We propose a physiochemical model for pyrolysis of levoglucosan using experimentally determined kinetic parameters for evaporation and polymerization of levoglucosan. After verifying the accuracy of the model, we used it to simulate behavior of levoglucosan under fast pyrolysis conditions. The simulation results showed that increasing the sample mass and applying higher heating rates promote polymerization of levoglucosan at the expense of evaporation. The detrimental effects of heating rate on levoglucosan evaporation suggest that although increased amounts of levoglucosan form during cellulose pyrolysis when higher heating rates are applied, much of the levoglucosan cannot be recovered as vapor because it turns into oligosaccharides that subsequently dehydrate to light oxygenates and char. Adopting experimental conditions that enhance the evaporation of levoglucosan, such as higher sweep-gas rates or reduced system pressures in combination with higher heating rates, is highly recommended for increasing levoglucosan recovery.